2022
DOI: 10.1101/2022.06.07.22276115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomics for the discovery of clinical delirium biomarkers: A systematic review of Major Studies

Abstract: Delirium represents a significant healthcare burden, diagnosed in over two million elderly Americans each year. In the surgical population, delirium remains the most common complication among elderly patients and is associated with longer hospital stays, higher costs of care, increased mortality and functional impairment. The pathomechanism of disease is poorly understood, with current diagnostic approaches somewhat subjective and arbitrary, and definitive diagnostic biomarkers are currently lacking. Despite t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This unbiased proteomic analyses of samples from a prior randomized control trial is the deepest unbiased plasma proteomic profiling for potential biomarkers of delirium to date [17]. We employed a rectangular biomarker workflow [43] to both discover and verify biomarkers of post-operative delirium (POD) on a single mass spectrometry platform without the use of traditional affinity-based verification methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This unbiased proteomic analyses of samples from a prior randomized control trial is the deepest unbiased plasma proteomic profiling for potential biomarkers of delirium to date [17]. We employed a rectangular biomarker workflow [43] to both discover and verify biomarkers of post-operative delirium (POD) on a single mass spectrometry platform without the use of traditional affinity-based verification methods.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike any other previous proteomic attempt to discover biomarkers of POD [17], we employed extensive HPLC fractionation on a PFP column [33] to increase coverage [90]. Although SOMAScan uses three dilution bins in order to cover the wide dynamic range of plasma [91],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to improve recognition and accurate case identification has seen a steady rise in recent years, although a small fraction of these attempts has focused on biomarker discovery. Most of these biomarker studies also employed targeted quantification strategies for a sub selected list of genes or proteins, an approach that is inherently biased and blinded to potentially novel factors involved in the etiology or consequences of delirium [17][manuscript].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated correlation between depth of anaesthesia measured using intra-operative processed EEG and postoperative neurocognitive outcomes [3]. Similarly, links between markers of systemic in ammation and neurocognitive outcomes have been explored using both targeted studies of candidate biomarkers and untargeted proteomics studies utilising high throughput multiplex assays [4]. As yet however, the link between systemic markers of in ammation, depth of anaesthesia and perioperative neurocognitive outcomes has not been the subject of prognostic modelling.…”
mentioning
confidence: 99%